Handbook of High‐resolution Spectroscopy 2011
DOI: 10.1002/9780470749593.hrs029
|View full text |Cite
|
Sign up to set email alerts
|

THz and Submillimeter‐wave Spectroscopy of Molecular Complexes

Abstract: This article reviews the recent progress of terahertz (THz) and submillimter‐wave (SMMW) spectroscopy in the frequency range of 10–300 cm −1 and its application to the study of weakly bound molecular complexes. The first section describes the light sources used for generating THz radiation, which includes the backward‐wave oscillators (BWO), the multipliers with the GaAs monolithic membrane diode (MOMED), and the supperlattice electronic devices (SLED), as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Another interesting topic is the hydrogen bond of liquid. For instance, the interaction between the two molecules within one water dimer (H 2 O) 2 , is much stronger than the Van der Waals force, which implies the existence of hydrogen bond with the typical energy at THz frequency range [119]. By applying the HATS method to study the ultrafast processes in water, the hydrogen dynamics are expected to be revealed.…”
Section: Hats For Solid and Liquid Mediamentioning
confidence: 99%
“…Another interesting topic is the hydrogen bond of liquid. For instance, the interaction between the two molecules within one water dimer (H 2 O) 2 , is much stronger than the Van der Waals force, which implies the existence of hydrogen bond with the typical energy at THz frequency range [119]. By applying the HATS method to study the ultrafast processes in water, the hydrogen dynamics are expected to be revealed.…”
Section: Hats For Solid and Liquid Mediamentioning
confidence: 99%
“…with n 1; 2; …; N : The absorption coefficient αν is finally obtained using the interpolated function f ν of F ν n and is therefore given by αν α max · f ν; (12) where the absorption maximum is given by α max αν 0 when the function f ν is set to unity at the resonance frequency f ν 0 1.…”
Section: A Absorption and Dispersion Line Shapesmentioning
confidence: 99%
“…We may mention here the highly accurate determinations of the ionization and bond dissociation energies of molecular hydrogen with submegahertz accuracy [4], the search for a time dependence of the fundamental constants of physics [5], the search for parity violation in chiral molecules [6,7], or fundamental questions related to the spectroscopy of atomic hydrogen [8]. While the quest for high precision concerns all spectral ranges from radiofrequency [9] to microwave and submillimeter wave spectroscopy toward XUV spectroscopy [10][11][12][13][14], microwave and gigahertz spectroscopy in the millimeter and submillimeter range has been traditionally a field of very high precision. High-precision analyses of gigahertz spectra have been discussed repeatedly for some decades, proposing a variety of techniques often in conjunction with the prototype molecules carbon monoxide (CO), carbon oxide sulfide (OCS), and others [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting early experimental example where intramolecular energy flow is in fact inhibited quite strongly was provided by the dissociation of the hydrogen bonded HF dimer, a minicluster, after excitation of the HF stretching overtones at energies exceeding the dissociation energy of about 12.7 kJ mol −1 by a factor of more than seven, still showing quite structured spectra indicating long lifetimes for vibrational predissociation [3,4] . Hydrogen bonded systems are intermediate cases between strong covalent bonds with binding energies of about 100 kJ mol −1 and larger, and weakly bonded van der Waals molecules such as (rare gas‐HF) complexes, [5] with binding energies of 1 to 3 kJ mol −1 , and simpler, very different dynamics. The current understanding of inhibited vibrational energy flow in (HFHF) systems is schematically shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%